2020
DOI: 10.52131/joe.2020.0202.0020
|View full text |Cite
|
Sign up to set email alerts
|

Banking Industry Specific Determinants of Financial Distress: Empirical Evidence from ASEAN Countries

Abstract: Recently, financial distress has become a significant issue, especially for the banking sector, that is considered as the backbone of the economy. Thus, the present study aim is to examine the effects of operating cash flow, profitability, financial leverage, trading activities and liquidity on financial distress of the banking industry of ASEAN countries. The researchers have extracted the data from the central banks of ASEAN countries for the year 2009 to 2018. The random effect model along with generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
3
0
6
Order By: Relevance
“…These findings support the traditional financial theory (Trade-off Theory), positing profitability as a key factor in achieving an optimal balance in a firm's capital structure (Said, 2022;Yakubu et al 2021). This study is in alignment with the research conducted by Yanti and Darmayanti (2019), Muflihah (2017), Saleem et al (2020), Kalbuana et al (2022), andAyu et al (2017), which collectively demonstrate a positive influence of profitability on financial distress prediction.…”
Section: Effect Of Profitability On Financial Distresssupporting
confidence: 90%
“…These findings support the traditional financial theory (Trade-off Theory), positing profitability as a key factor in achieving an optimal balance in a firm's capital structure (Said, 2022;Yakubu et al 2021). This study is in alignment with the research conducted by Yanti and Darmayanti (2019), Muflihah (2017), Saleem et al (2020), Kalbuana et al (2022), andAyu et al (2017), which collectively demonstrate a positive influence of profitability on financial distress prediction.…”
Section: Effect Of Profitability On Financial Distresssupporting
confidence: 90%
“…Ownership can be split into some different types like family based, government-owned and foreign operating owned, etc. The research conducted in bank it was found that the state owned and foreign owned have an effect that is negatively linked on the dividends, in family ownership it has an effect that was positively linked with dividend payouts and in family-owned banks dividends was paid in excess to the shareholders and an effect that is negatively linked on dividend payouts in controlling ownerships in accordance to (Saleem, Hussain, & Ibraheem, 2020;Setiawan, Aryani, Yuniarti, & Brahmana, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial distress merupakan tahap penurunan kondisi keuangan suatu perusahaan sebelum kebangkrutan terjadi. Financial distress dapat terjadi saat perusahaan tidak mampu mengelola anggaran arus kas dan berbagai faktor lain seperti manajemen yang tidak kompeten atau kendala perusahaan yang dapat mengganggu keseimbangan financial distress (Saleem et al, 2020). Perusahaan yang mengalami financial distress dapat menurunkan profitabilitas dan memberikan dampak terhadap arus kas perusahaan (Jaafar et al, 2018).…”
Section: Pendahuluanunclassified
“…Dengan perusahaan mengetahui kondisi keuangan, maka perusahaan dapat mengatasi kondisi tersebut. (Ikpesu, 2019;Wesa dan Otinga, 2018;Saleem et al, 2020) dalam penelitiannya menemukan hasil likuiditas berpengaruh negatif terhadap financial distress. Hasil penelitian ini tidak sesuai dengan penelitian (Kazemian et al, 2017;Waqas dan Rus, 2018;Zelie dan Wassie, 2019) yang menemukan likuiditas berpengaruh positif terhadap financial distress.…”
Section: Pendahuluanunclassified